2006
DOI: 10.1177/0734242x06067322
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic painting residues as an alternative raw material for red clay industry

Abstract: In this study, the viability of using electrostatic painting residues--paint sludge--as a raw material to the red clay industry was investigated. Red clay-based ceramic masses containing electrostatic paint residues were formulated during the study. The clays were obtained from the Rio do Rastro deposit, in Gravataí, and were of the standard formulation used in industry. Different ceramic mass formulations with additions of 0.5, 1.0, 2.5 and 5.0 wt.% electrostatic painting residue in addition to a formulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Although the PBW of this study has chemical and mineralogical characteristics similar to those characterized by other researches 8 , 10 , 11 , 23 , here are no reports in the literature of investigations about their peculiar granulometry (i.e. they have a portion of fine material and aggregates of different sizes).…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Although the PBW of this study has chemical and mineralogical characteristics similar to those characterized by other researches 8 , 10 , 11 , 23 , here are no reports in the literature of investigations about their peculiar granulometry (i.e. they have a portion of fine material and aggregates of different sizes).…”
Section: Introductionsupporting
confidence: 62%
“…Similar results were verified 11 where it was found that the incorporation of 20% automotive paint waste in bituminous mixtures did not cause significant changes in the mechanical properties, compared to the reference mixtures. Also, considering that industrial paint waste has a porous microstructure 5 , 10 , the mixture with a content of 40% PBW reduced the average strength of 19.73%, when compared with mixing (0% PBW) possibly caused by voids in the concrete matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation